Development of a model evaluation protocol for CFD analysis of hydrogen safety issues the SUSANA project. (16th March 2017) - Baraldi, D.; Melideo, D.; Kotchourko, A.; Ren, K.; Yanez, J.; Jedicke, O.; Giannissi, S.G.; Tolias, I.C.; Venetsanos, A.G.; Keenan, J.; Makarov, D.; Molkov, V.; et al.
Abstract: The "SUpport to SAfety aNAlysis of Hydrogen and Fuel Cell Technologies (SUSANA)" project aims to support stakeholders using Computational Fluid Dynamics (CFD) for safety engineering design and assessment of FCH systems and infrastructure through the development of a model evaluation protocol. The protocol covers all aspects of safety assessment modelling using CFD, from release, through dispersion to combustion (self-ignition, fires, deflagrations, detonations, and Deflagration to Detonation Transition - DDT) and not only aims to enable users to evaluate models but to inform them of the state of the art and best practices in numerical modelling. The paper gives an overview of the SUSANA project, including the main stages of the model evaluation protocol and some results from the on-going benchmarking activities. Highlights: A Hydrogen Model Evaluation Protocol or HYMEP was developed for the 1st time. HYMEP is intended for the evaluation of CFD models for hydrogen safety issues. HYMEP is supported by a verification database and a validation database. HYMEP is supported by complimentary documents: state of the art, best practice, etc.